a)
b)
Răspunsuri la întrebare
Răspuns de
1
27^[(2x-1)/x]=9^(2x-1)
(3^3)^[(2x-1)/x]=(3^2)^(2x-1)
3^[3*(2x-1)/x]=3^[2*(2x-1)]
3*(2x-1)/x=2*(2x-1)
6x-3=4x^2-2x
4x^2 -8x+3=0
(2x-3)(2x-1)=0
x={1/2;2/3}
(3^3)^[(2x-1)/x]=(3^2)^(2x-1)
3^[3*(2x-1)/x]=3^[2*(2x-1)]
3*(2x-1)/x=2*(2x-1)
6x-3=4x^2-2x
4x^2 -8x+3=0
(2x-3)(2x-1)=0
x={1/2;2/3}
barbie18:
ce inseamna ^?
Alte întrebări interesante
Engleza,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă